Pengaruh Pendidikan Kesehatan Metode Demonstrasi Terhadap Keterampilan Balut Bidai Penanganan Fraktur Pada Anggota PMR SMA Negeri 1 Banyudono - Wahyu Ramadhani, Berliana; Rima Agustin, Wahyu; Murharyati, Atiek (JINTAN: Jurnal Ilmu Keperawatan, 2025)
Severed contuinity including cartilage, which must be treated quickly, appropriately, and according to the procedure is called fracture. Fractures have common symptoms such as pain or pain, swelling, and changes in body shape. Splint dressing is a technique of defending or mobilizing injured body parts using rigid and flexible objects. Aims to find out how the demonstration method health education had impact on the skills of splint wraps handling fractures in PMR members of Banyudono 1 Public High School in addition, splint wrapping assistance can be done by anyone who is trained. PMR members of Banyudono 1 Publlic High School in addition, splint wrapping assistance can be done by anyone who is trained. This study used the population of PMR members of Banyudono 1 Public High School, carried out by the total sampling method, a total sample of 43 respondents. This type of research is quantitative with a quasy experiment design, this research design uses one group pretest-posttest design without control. The results of the splint wrap pretest showed that the majority of respondents were in the category of less than 41 respondents (95.3%), and the posttest score after being given health education showed that the majority of respondents were in the category of quite skilled as many as 39 respondents (90.7%). The results of the Wilcoxon test show p value (0.000) < 0.05. It can be concluded that there is an influence of demonstration method health education on splint dressing skills for fracture management among PMR members of Banyudono 1 Public High School.